2018
DOI: 10.1634/theoncologist.2017-0348
|View full text |Cite
|
Sign up to set email alerts
|

Safety Profile of Biosimilar Filgrastim (Zarzio/Zarxio): A Combined Analysis of Phase III Studies

Abstract: The biosimilar filgrastim EP2006 (Zarzio, Zarxio, biosimilar filgrastim-sndz) has been approved in Europe since 2009 and in the U.S. since 2015. This combined analysis of two phase III studies provides additional clinical evidence that the biosimilar filgrastim EP2006 has a safety profile consistent with previous studies of reference filgrastim and supports large postmarketing studies of EP2006 in Europe. Strengthening the evidence for biosimilar filgrastim can help improve acceptance of biosimilars and increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The safety profile for the reference and switched groups in this study was in line with the known safety profile for the reference, with musculoskeletal/connective tissue disorders the most frequently reported AEs associated with filgrastim. A pooled analysis of the two pivotal registration trials with EP2006 showed similar efficacy and safety results [10] to findings of studies carried out for the reference product.…”
Section: Discussionmentioning
confidence: 51%
“…The safety profile for the reference and switched groups in this study was in line with the known safety profile for the reference, with musculoskeletal/connective tissue disorders the most frequently reported AEs associated with filgrastim. A pooled analysis of the two pivotal registration trials with EP2006 showed similar efficacy and safety results [10] to findings of studies carried out for the reference product.…”
Section: Discussionmentioning
confidence: 51%
“…18 A recently published combined analysis of this and another phase III trial on the safety of filgrastim-sndz in patients with breast cancer concluded that filgrastim-sndz has a safety profile consistent with previous studies of reference filgrastim. 22 Several retrospective studies also report similar efficacy between filgrastim-sndz and filgrastim for prophylaxis of chemotherapy-induced neutropenia. [23][24][25][26] Based on these data, filgrastim-sndz is included in the NCCN Guidelines as an appropriate substitute for filgrastim.…”
Section: Biosimilarsmentioning
confidence: 84%
“…10 A number of studies using clinical trial and real-world evidence data have demonstrated the similar efficacy, effectiveness, and safety between biosimilar and reference filgrastim. [11][12][13][14] In addition, Grewal et al and McBride et al developed theoretical frameworks and showed potential cost savings for filgrastim products in the US market. 15,16 But real-world evaluations in the uptake and cost savings of biosimilar filgrastim-sndz in nationally representative populations remain limited.…”
Section: What This Study Addsmentioning
confidence: 99%